Participatory Governance? A Critical Perspective on Stakeholder Knowledge Integration in the Context of German Baltic MPAs - Neele Neddersen; Josefine B. Gottschalk; Michael Kriegl; Heike Schwermer (Ocean and Society)
The ocean is under increasing pressure from various human activities, including overfishing, pollution, and climate change. In response to these challenges, marine protected areas (MPAs) have emerged as important and widely applied tools for conserving and restoring marine ecosystems. Considering the complexity of identifying appropriate management measures and the resulting dynamics of their implementation, the integration of various knowledge types is of crucial importance. Germany has evolved as a leading advocate for marine conservation, playing an influential role in global conservation efforts. This context provides an interesting opportunity for examining the social and political dynamics of MPA implementation. In this study, we investigate the role of participatory approaches to knowledge integration using the case of two MPAs located in the German exclusive economic zone of the Baltic Sea. To this end, we conducted and analyzed 13 interviews with stakeholders from fisheries, environmental protection, public administration, and science. This approach was complemented by the review of documents leading to the adoption of the management plans. Our research addresses two key questions: (a) How much and what kind of knowledge is included in the management plan of the two German Baltic Sea MPAs and (b) how does this institutional framework promote or hinder the integration of diverse knowledge types? Our findings highlight the obstacles (e.g., power imbalances between different participation levels) of participatory governance levels in the two German MPAs. Thus, this study provides valuable insights for enhancing the effectiveness of participatory governance in German MPAs, thereby advancing marine conservation efforts.